WRITING RECOUNT TEXT USING COOPERATIVE SCRIPT: STUDENTS' DIFFICULTIES - Sartika Sartika; Rissa San Rizqiya (PROJECT (Professional Journal of English Education), 2021)
The objective of the research is to find out the students' difficulties in learning writing recount text using the cooperative script. This research used a qualitative method and the design was descriptive qualitative. The respondents of the research were 15 tenth grade students of Senior High School in Cikadu. The data were obtained from tests and interviews. The results of the research show that the students' difficulties in learning writing recount text using the cooperative script in mechanics, such as punctuation and capital letter. Implies that mechanic aspect tends to be ignored in learning. Keywords:  Cooperative Script, Writing, Students’ Difficulties